Aberrant Periodontal and Systemic Immune Response of Overweight Rodents to Periodontal Infection. (3rd January 2019) - Yu, Ting; Zhao, Li; Huang, Xin; Xie, Baoyi; Zhang, Jincai; Xuan, Dongying
Abstract : This study aimed to explore periodontal and systemic immune response of overweight hosts to periodontitis. Forty C57 BL/6J male mice were divided into high (HF) or low fat (LF) diet groups and fed with the two diets, respectively, for 8 weeks. Each diet group was then divided into periodontitis (P) or control (C) groups (n = 10 per group) for 10-day ligation or sham-ligation. Overweight-related parameters including body weight were measured. Alveolar bone loss (ABL) was morphometrically analyzed and periodontal osteoclasts were stained. Periodontal immune response including leukocyte and macrophage number and inflammatory cytokines were analyzed by histology and quantitative PCR. Serum cytokine and lipid levels were quantified using electrochemiluminescence immunoassays, enzyme-linked immunosorbent assays, and biochemistry. It was found that HF group had 14.4% body weight gain compared with LF group ( P < 0.01). ABL and periodontal osteoclast, leukocyte, and macrophage number were higher in P group than C group regardless of diet ( P < 0.05). ABL and periodontal osteoclast number were not affected by diet regardless of ligation or sham-ligation. Leukocyte and macrophage number and protein level of tumor necrosis factor α (TNF- α ) in periodontium and serum interleukin-6 level were downregulated by HF diet in periodontitis mice ( P < 0.05). Periodontal protein level of TNF- α was highly correlated with serum interleukin-6 and low-density lipoprotein cholesterol levels ( P < 0.01). These findings indicated that impaired immune response occurs both periodontally and systemically in preobesity overweight individuals. Given a well-reported exacerbating effect of obesity on periodontitis, overweight, if let uncontrolled, might place the individuals at potential risk for future periodontal tissue damage.